2022
DOI: 10.1007/s11069-022-05433-5
|View full text |Cite
|
Sign up to set email alerts
|

Unzipping flood vulnerability and functionality loss: tale of struggle for existence of riparian buildings

Abstract: Floods pose significant risk to riparian buildings as evidenced during many historical events. Although structural resilience to tsunami flooding is well studied in the literature, high-velocity and debris-laden floods in steep terrains are not considered adequately so far. Historical floods in steep terrains necessitate the need for flood vulnerability analysis of buildings. To this end, we report vulnerability of riparian-reinforced concrete buildings using forensic damage interpretations and empirical/analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 32 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…For example, excessive sand mining adversely impacts water quality, altering sediment transport and causing riverbed instability [27,28]. It can exacerbate flooding, shaking nearby structures and threatening communities along riverbanks [29][30][31]. The removal of sand from rivers significantly impacts various environmental aspects [32].…”
Section: Introductionmentioning
confidence: 99%
“…For example, excessive sand mining adversely impacts water quality, altering sediment transport and causing riverbed instability [27,28]. It can exacerbate flooding, shaking nearby structures and threatening communities along riverbanks [29][30][31]. The removal of sand from rivers significantly impacts various environmental aspects [32].…”
Section: Introductionmentioning
confidence: 99%
“…Climate change alters temperature, precipitation, glacier melting and discharge of river networks (Hock et al 2019) and fetches cascading ood havoc (Maharjan et al 2021). Climate induced extreme precipitation event has led to catastrophic ood (Zhang et Except climate attributes, the oods are more comprehensive and cascading in nature (Gautam et al 2022). In Landslide damming ood, large volume of water and sediments erosion leads to change geomorphology of bedrock and alluvial rivers (Lin et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Several researcheshaveshown that the lack of implementation of code and bye-laws are the main reason behind the increasing collapse of structures during earthquakes (Anhorn et al, 2015;Giri, 2013;Mishra, 2019;Sehgal apoorva., 2017). It was also observed that lowquality materials used in construction sites lead to building defects and to ensure a good quality of work it is important to use the acceptable material in construction works (Ahzahar et al, 2011).Not only earthquakes, floods and landslides (Darchula 2013 (Paudel et al, 2013),Melamchiriver flood (2021) (Gautam et al, 2022))also destroy buildings. One study (Kumar et al, 2012)studied the seismic hazard and risk assessments of Nepal with the help of GIS platformand this study found that the high percentage of permanent houses in the five districts are Darchula, Kathmandu, Doti, Baitadi and Baglungwere exposed to a very high hazard zone.…”
Section: Introductionmentioning
confidence: 99%